Avian Egg Timers: Female Cowbirds Judge Past, Present, and Future When Making Nest Parasitism Decisions - White, David J. (Frontiers in Ecology and Evolution, 2020)
The cognitive demands associated with brood parasitism are substantial. Not only must female parasites locate nests and assess their suitability for parasitism, they must also time parasitism to correspond with the breeding behavior of the host. Keeping track of the reproductive state of hosts for a variety of nests allows the parasite to select a nest where their egg can be incubated successfully. Thus, nest selection decisions are integral to obligate brood parasites’ reproductive success. In captive breeding flocks of brown-headed cowbirds (Molothrus ater), I studied (1) females’ abilities to time a host nest’s readiness for parasitism and (2) the timing of females’ nest selection decisions. I found that cowbirds can attend to the amount of time that elapsed since a host egg was added to a nest and can use that information to choose a nest for parasitism. Females made their choice of nest during prospecting the day before they laid, and, once decided, they did not update their decisions on the day of laying. Taken together, the results reveal that female cowbirds process substantial amounts of information about location, time, number, and rate in order to plan for future parasitism. This research program reveals that species-typical decisions integrate a variety of general and specialized cognitive abilities to allow females to behave adaptively and maximize reproductive success.